An overview engineering properties of sediments and submarine mass movements in the Hazar Lake (Elazığ/Eastern Turkey) - Aslan Topçuoğlu, Yasemin; Gürocak, Zülfü (Gumushane University, 2021)
The aim of this study is to determine the engineering properties of the sediments and the submarine mass movements that are formed in the one of the most important tectonic lake of Turkey, Hazar Lake, located in the East Anatolian Fault Zone. For this purpose, laboratory experiments were carried out on undisturbed soil samples taken from the points that were determined by using high-resolution seismic data of the lake. According to the results of the experiments, the soils at the areas where streams discharge into Hazar Lake are Non-Plastic Course Silt (MLN), and around the mid-parts of the lake is High Plastic Silt (MH). Dry unit weight values of soils increase with depth, while porosity and void ratio values decrease. The strength value of MLN is much higher than MH type soils. The strength of MH type soil is quite low since it is not tightened enough. In the seismic profiles of Hazar Lake, the soil thickness is about maximum 3 m on steep slopes, while the soil thickness can reach up to 10 m on slopes having lower dips. On the slopes where the soil thickness is higher, submarine mass movements developed by the own weight of the soil especially. These types of mass movements are slumptype slides in which traces of plastic deformation and circular failure surfaces are clearly visible. Considering that the soil strength on the slopes of Hazar Lake are very low, it can be said that these mass movements were formed by the weight of the sediments and, the earthquakes that took place in the Eastern Anatolian Fault Zone (DAFZ) also catalyze these mass movements to occur. © 2021, Gumushane University. All rights reserved.
Hazar Gölü’ndeki (Elazığ/Doğu Türkiye) çökellerin mühendislik özelliklerine ve sualtı kütle hareketlerine genel bir bakış
Keywords: East Anatolian fault zone; Elazığ region; Hazar lake; Soil; Submarine mass movement